Incorporation of nickel into synthetic goethites and the stabilisation of mineral precursor phases - implications for natural systems - Rachel L. Norman (2014)
Over 70% of the Earth s economically recoverable nickel (Ni) resides in laterite ore deposits, however they account for less than half of the current global nickel production. During laterization, nickel and other soluble ions are taken into solution before re-precipitating within iron oxide minerals in the limonite zone, or as serpentines and other phyllosilicates in the layers below this zone. It is these laterite deposits that show the greatest potential for low energy, environmentally conscious processing. The major host of nickel in the limonite zone is the iron-oxyhydroxide mineral goethite, α-FeOOH, where up to 4 mol% Ni has been reported in natural specimens, and even higher levels in synthetic samples (5.5 mol%). The Ni is assumed to be incorporated in the crystal structure of the goethite, but previous characterisation work only demonstrated a weak to moderate correlation of mineral structure change with the nickel content in goethite. Mining companies working on the extraction and recovery of nickel from the limonite zone of lateritic deposits have noticed that the ease with which nickel can be extracted varies greatly; goethite rich ores that appear to have similar mineralogies/geologies can display extreme variation in their leachability. It is not clear why the ores behave in this way, but in order for extraction techniques and subsequent recovery of nickel to be improved, the reasons behind this variability need to be understood. The lateritic ore materials from which nickel is extracted are generally made up of a number of different mineral phases. The multiphase nature of the samples means that characterisation of the goethite-type phases from these materials is challenging. To simplify the system and allow the association of Ni into goethite and/or other iron oxyhydroxide phases to be studied in a controlled environment, a synthetic study was carried out. Ni-bearing goethites have been synthesised at a series of different temperatures and characterised by a range of analytical techniques including PXRD, IR, Raman, TGA, ICP-OES, SEM and TEM. It was found that a second phase, ferrihydrite, co-existed with the goethites, the proportion of which increased at lower synthesis temperatures and with increasing amounts of Ni. Ferrihydrite is known to be a precursor phase in the formation of goethite, but its poorly crystalline nature makes it difficult to identify using standard characterisation techniques such as PXRD. The introduction of Ni to the system increases the stability of the ferrihydrite phase, inhibiting its transformation to goethite. It is believed that some of the Ni thought to be incorporated into goethite could actually reside in an undetected ferrihydrite phase, which could account for the differences observed in the leachability of natural materials. Characterisation techniques were investigated to try and determine a simple way to identify ferrihydrite in these systems, which could ideally be used in the field to identify the presence of ferrihydrite in goethite rich ore materials. Thermal analysis proved to be particularly promising as a technique which could be used to identify ferrihydrite rich deposits before extraction, enabling the most efficient and environmentally conscious metal recovery process for each deposit to be identified. In order to investigate the way in which Ni partitions itself between structural incorporation into goethite and association with a secondary ferrihydrite phase, a new washing technique was developed using EDTA, which is capable of selectively removing the ferrihydrite phase whilst leaving the goethite intact. This investigation suggests that a maximum of ~2.5 mol% of Ni is structurally incorporated into goethite, regardless of how much is added during the synthesis. Any excess nickel, above that which is substituted into the goethite structure, was found to be associated with the poorly crystalline ferrihydrite phase. Despite being considered a metastable phase, the increased stability of ferrihydrite resulting from the presence of Ni suggests that it may persist in laterite deposits within geological systems. If ferrihydrite is indeed present in nickeliferous laterites, it may be a significant host for Ni, and potentially many other critical elements. Based on the methodology developed whilst studying synthetic samples, a characterisation program for materials from lateritic ore deposits was conducted to investigate the presence of ferrihydrite in natural systems. From the research presented and discussed in this thesis, proof of the presence or absence of ferrihydrite in laterite systems, causing variations in the leachability of the ore materials, could not be conclusively established. The thermal analysis technique developed here successfully identified and quantified ferrihydrite in the presence of goethite in synthetic systems, and showed great potential when used to characterise the lateritic goethite samples, certainly suggesting that ferrihydrite could be present in these natural ore materials. With further refinement of the methodology, to enable a larger range of sample types to be accurately analysed, TGA is a technique which could be used as a screening tool for laterite ores.